Social Worker Interventions to Strengthen Family and Community Support for Improving Medication Adherence Among Hypertension Patients in RW 02, Kuta Baru Village: Intervensi Pekerja Sosial Dalam Menguatkan Dukungan Keluarga dan Kelompok Untuk Meningkatkan Kepatuhan Minum Obat Penderita Hipertensi di RW 02 Kelurahan Kuta Baru - Dhepita Septiyani; Mari Esterilita (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Non-compliance with medication among hypertensive patients in RW 02, Kuta Baru Village, has become a social and health issue triggered by the residents' busy economic activities as laborers and traders, as well as the weak family support system. This community service activity aims to address how family and environmental support, as well as community knowledge, influence medication adherence among hypertensive patients through macro social worker intervention using a multidisciplinary collaborative approach with pharmacy and midwifery students. The method used is community empowerment with stages of social initiation, social organization, social assessment, social planning, social intervention, to evaluation and termination. The intervention is focused on 1) Utilizing alarms on cell phones as a disciplinary tool, 2) Establishing family-based Medication Supervisors, and 3) Activating support groups through PKK cadres and WhatsApp Groups. The evaluation results using the Paired Samples T-Test on 17 key respondents showed an increase in health literacy, where the average knowledge score increased from 41.2% (pre-test) to 83.5% (post-test). This community service proved that strengthening a social support system integrated with simple technology can change residents' perceptions from curative treatment to preventive control. This community service resulted in the independence of cadres and families in monitoring the health of patients to prevent complications of hypertension on an ongoing basis.